Características bio-ecológicas en poblaciones de lombrices (Oligochaeta: Glossoscolecidae) de una sabana natural y una protegida en los llanos centrales de Venezuela - Hernández, Luis (2012)
Bioecological characteristics of earthworm populations (Oligochaeta: Glossoscolecidae) in a natural and a protected savanna in the central Llanos of Venezuela. In tropical savannas, the earthworm communities have a predominant role since they regulate the soil structure and dynamics of the organic matter. To study the effect on earthworm populations in two differently managed savannas, we compared the general aspects of the biology and ecology of earthworm populations from a 40 years protected savanna (SP) with no fire or cattle raising at the Estación Biológica de los Llanos, Venezuela (EBLL), and a natural savanna (SNI), under normal burning and cattle raising management conditions. Sampling was carried out at the end of the dry season (April), and at the peak of the wet season (July-August). The main physical properties of soils per system were estimated. In each system, in plots of 90x90m, five fixed sampling units were selected at random; and at each sampling point one soil monolith of 25x25x30cm was collected per unit. Earthworms were extracted using the hand sorting extraction method; and the flotation method was used to estimate the density of cocoons. The earthworms were classified in different ecological categories considering their pigmentation, size and depth profile distribution. As a result of the savanna protection, physical parameters were modified in relation to SNI. The SP soils had higher soil moisture when compared to SNI. Soil moisture varied with depth during the dry season since, after the start of the rainy season, the soil was saturated. Field capacity in the SP was greater than that in the SNI. The surface apparent bulk density of soil was lower in the SP respect SNI, reflecting a lower soil compaction. Total average for the density and biomass of earthworms differed greatly, showing higher values in the SP. The earthworm density average in SP ranged between 25.6-85 individuals/m2 and the average biomass between 6.92-23.23g/m2. While in SNI, earthworms were only found in August, with a mean density of 22.40individuals/m2 and a mean biomass of 5.17g/m2. The vertical distribution pattern was only analyzed for the SP, and as in the SNI, no earthworms were found during the dry season; in the SP, a migration of earthworms to deeper layers during the dry season was observed; while in the rainy season they moved to upper soil layers to feed. The systems were characterized by abundance in juvenile Glossoscolecidae family earthworms which might be included in the endo-anecic ecological category. Results suggest that savanna agricultural management can modify an important fraction of pedofauna, particularly their earthworm communities, by modification of soil properties.